Validasi Metode dan Penetapan Kadar Sirup Kering Cefadroxil dengan Metode FTIR-ATR - Rahmasari, Khusna Santika; Alfarizi, Muhammad Bahtiar (Universitas Hamzanwadi, 2023)
Cefadroxil is a broad-spectrum bactericidal antibiotic belonging to the first group of cephalosporins produced by the fungus Cephalosporium acremonium. This study aims to validate the method and determine the concentration of cefadroxil dry syrup using FTIR-ATR. The method used is FTIR-ATR with aquabides as a solvent. Parameter Validation of the analysis method carried out includes linearity, accuracy, precision, Limit of Detection (LOD) and Limit of Quantification (LOQ). The results of the linearity test show a value of r = 0.999 which indicates linear. The accuracy obtained is 97 - 105.5%. Precision with an Relative Standard Deviation (RSD) value of 0.54%, LOD of 469.72 µg/mL and LOQ of 1423.6 µg/mL. The results of determining the levels of cefadroxil dry syrup with three samples, namely sample A 100.2%; sample B 100.5%; sample C 100.1%. Based on the research results, it can be concluded that the FTIR-ATR method is valid and the sample concentration complies with the provisions of the Indonesian Pharmacopoeia Edition VI, namely the concentration of cefadroxil in dry syrup preparations is not less than 90% and not more than 120%.